Perspectives of Physician and Pharmacist Stewards on Successful Antibiotic Stewardship Program Implementation: A Qualitative Study. (15th June 2020) - Barlam, Tamar F; Childs, Ellen; Zieminski, Sarah A; Meshesha, Tsega M; Jones, Kathryn E; Butler, Jorie M; Damschroder, Laura J; Goetz, Matthew Bidwell; Madaras-Kelly, Karl; Reardon, Caitlin M; Samore, Matthew H; Shen, Jincheng; et al.
Abstract: Background: Antibiotic stewardship programs (ASPs) are required at every hospital regardless of size. We conducted a qualitative study across different hospital settings to examine perspectives of physician and pharmacist stewards about the dynamics within their team and contextual factors that facilitate the success of their programs. Methods: Semistructured interviews were conducted in March–November 2018 with 46 ASP stewards, 30 pharmacists, and 16 physicians, from 39 hospitals within 2 large hospital systems. Results: We identified 5 major themes: antibiotic stewards were enthusiastic about their role, committed to the goals of stewardship for their patients and as a public-health imperative, and energized by successful interventions; responsibilities of pharmacist and physician stewards are markedly different, and pharmacy stewards performed the majority of the day-to-day stewardship work; collaborative teamwork is important to improving care, the pharmacists and physicians supported each other, and pharmacists believed that having a strong physician leader was essential; provider engagement strategies are a critical component of stewardship, and recommendations must be communicated in a collegial manner that did not judge the provider competence, preferably through face-to-face interactions; and hospital leadership support for ASP goals and for protected time for ASP activities is critical for success. Conclusions: The physician-pharmacist team is essential for ASPs; most have pharmacists leading and performing day-to-day activities with physician support. Collaborative, persuasive approaches for ASP interventions were the norm. Stewards were careful not to criticize or judge inappropriate antibiotic prescribing. Further research should examine whether this persuasive approach undercuts provider appreciation of stewardship as a public health mandate. Abstract : This study examines the implementation of antibiotic stewardship programs (ASPs) across diverse settings to explore factors that facilitated program success. Qualitative interviews with physician and pharmacist stewards identified different roles and perspectives that should be considered during implementation of ASPs.